Immobilization of heavy metal in coal bottom ash (CBA) mortar - Kamal N.L.M.; Beddu S.; Zahari N.M.; Syamsir A.; Itam Z.; Mohamad D.; Sadon S.N.; Yang K.J.; Manan T.S.B.A. (American Institute of Physics Inc., 2023)
Coal bottom ash (CBA) is a coal combustion by-products produced by coal-fired power plants. It is an alternative for cement material whilst reducing greenhouse effect. This research aims to investigate immobilization of heavy metal in concrete mortar contained of CBA. The solidification/stabilization (S/S) method was applied for the immobilization purpose. Chemical bonding and the functional group of the CBA mortar were comparable to the OPC cement mortar as negative control. Thus, CBA has good potential as eco-friendly cement binder for a better environment. 2019 Author(s).